Insecticidal Activity Evaluation of Phenylazo and Dihydropyrrole-Fused Neonicotinoids Against Cowpea Aphids Using the MLR Approach - Simona Funar-Timofei; Alina Bora (Proceedings, 2019)
This paper presents a Quantitative Structure-Activity Relationship (QSAR) study of a series of 24 dihydropyrrole-fused and phenylazo neonicotinoid derivatives, with insecticidal activity tested against Cowpea aphids (Aphis craccivora). In this regard, the conformational search ability of the OMEGA software was employed to model neonicotinoid conformer ensembles, using molecular mechanics calculations based on the 94s variant of the Merck Molecular force field (MMFF94). The minimum energy conformers were used to calculate structural descriptors, which were further related to the insecticidal activity (pLC50 values), using the multiple linear regression (MLR) approach. The genetic algorithm was used for variable selection and several criteria for internal and external model validation. A robust model (r2 = 0.880, r2adj = 0.855, q2LOO = 0.827, s = 0.2098, F = 34.295) with predictive power (concordance correlation coefficient (CCC)ext = 0.945, r2m= 0.824) was obtained, using the QSARINS software. The developed model can be confidently used for the prediction of the insecticidal activity of new chemicals, saving a substantial amount of time and money.